Faktor – Faktor Yang Mempengaruhi Pemahaman Penerapan SAK EMKM pada Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) Di Kecamatan Tanjung Karang Pusat - Rahmadianti, Syahra Surya; Maryani, Maryani; Pentiana, Destia (Reviu Akuntansi, Manajemen, dan Bisnis, 2024)
Purpose: This study aimed to understand the implementation of the SAK EMKM among MSME actors in the Tanjung Karang Pusat District. Methodology/Approach: This study used quantitative research methods with a field study approach. The research population consisted of MSME actors in Tanjung Karang Pusat District, Bandar Lampung City, totaling 4,402 MSME units. Data were collected through interviews, observations, and the use of questionnaires, whose validity and reliability were tested. Results: The results obtained from this research paint a vivid picture, revealing that the effectiveness of SAK EMKM implementation within the ambition of Bandar Lampung City is significantly shaped and influenced by the degree of socialization of these standards. Furthermore, the educational attainment of MSME operators and the duration of their business establishment have emerged as pivotal factors that profoundly impact their understanding and practical application of SAK EMKM. In essence, this research reveals a multifaceted landscape of influences that intersect and converge within the dynamic world of MSMEs, casting light on the intricate relationships between financial standards, educational backgrounds, and temporal aspects of business development in Bandar Lampung City. Limitations: The involvement of MSME researchers in Tanjung Karang Pusat District. Contribution: The researcher’s contribution to factors that influence the understanding of the implementation of SAK EMKM.